2012
DOI: 10.1007/s00421-012-2326-8
|View full text |Cite
|
Sign up to set email alerts
|

A perceptually regulated, graded exercise test predicts peak oxygen uptake during treadmill exercise in active and sedentary participants

Abstract: The validity of predicting peak oxygen uptake ([Formula: see text]) in sedentary participants from a perceptually regulated exercise test (PRET) is limited to two cycle ergometry studies. We assessed the validity of a treadmill-based PRET. Active (n = 49; 40.7 ± 13.8 years) and sedentary (n = 26; 33.4 ± 13.2 y) participants completed two PRETS (PRET 1 and PRET2), requiring a change in speed or incline corresponding to ratings of perceived exertion (RPE) 9, 11, 13 and 15. Extrapolation of RPE: [Formula: see tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…Thus, ratings of perceived exertion assessed during load-incremented submaximal exercise tests have the potential to be used in statistical models to predict VO 2peak . A number of studies have demonstrated the utility of the Borg 15 Category Scale in prediction of maximal oxygen consumption or VO 2peak from ratings of perceived exertion determined during field tests (Davies, Rowlands, & Eston, 2008), perceptually regulated exercise bouts (Eston, Lamb, Parfitt, & King, 2005; Eston, Faulkner, Mason, & Parfitt, 2006; Faulkner, Parfitt, & Eston, 2007; Eston, Lambrick, Sheppard, & Parfitt, 2008; Morris, Lamb, Hayton, Cotterrell, & Buckley, 2010; Al-Rahamneh & Eston, 2011b; Eston, Evans, Faulkner, Lambrick, Al-Rahamneh, & Parfitt, 2012) and graded exercise tests (Dunbar & Bursztyn, 1996; Okura & Tanaka, 2001; Faulkner & Eston, 2007; Coquart, Lemaire, Dubart, Douillard, Luttenbacher, Wibaux, et al , 2009; Lambrick, Faulkner, Rowlands, & Eston, 2009; Coquart, Eston, Grosbois, Lemaire, Dubart, Luttenbacher, et al , 2010; Al-Rahamneh & Eston, 2011a; Al-Rahamneh, Faulkner, Byrne, & Eston, 2011). Faulkner and Eston (2007) reported an accurate prediction of maximal oxygen consumption using ratings of perceived exertion for the overall body (Borg 15 Category Scale) determined during a load-incremented submaximal cycle ergometer protocol involving men and women of high and low fitness levels.…”
mentioning
confidence: 99%
“…Thus, ratings of perceived exertion assessed during load-incremented submaximal exercise tests have the potential to be used in statistical models to predict VO 2peak . A number of studies have demonstrated the utility of the Borg 15 Category Scale in prediction of maximal oxygen consumption or VO 2peak from ratings of perceived exertion determined during field tests (Davies, Rowlands, & Eston, 2008), perceptually regulated exercise bouts (Eston, Lamb, Parfitt, & King, 2005; Eston, Faulkner, Mason, & Parfitt, 2006; Faulkner, Parfitt, & Eston, 2007; Eston, Lambrick, Sheppard, & Parfitt, 2008; Morris, Lamb, Hayton, Cotterrell, & Buckley, 2010; Al-Rahamneh & Eston, 2011b; Eston, Evans, Faulkner, Lambrick, Al-Rahamneh, & Parfitt, 2012) and graded exercise tests (Dunbar & Bursztyn, 1996; Okura & Tanaka, 2001; Faulkner & Eston, 2007; Coquart, Lemaire, Dubart, Douillard, Luttenbacher, Wibaux, et al , 2009; Lambrick, Faulkner, Rowlands, & Eston, 2009; Coquart, Eston, Grosbois, Lemaire, Dubart, Luttenbacher, et al , 2010; Al-Rahamneh & Eston, 2011a; Al-Rahamneh, Faulkner, Byrne, & Eston, 2011). Faulkner and Eston (2007) reported an accurate prediction of maximal oxygen consumption using ratings of perceived exertion for the overall body (Borg 15 Category Scale) determined during a load-incremented submaximal cycle ergometer protocol involving men and women of high and low fitness levels.…”
mentioning
confidence: 99%
“…The Polar FT1 HR monitor and a Polar T31-Coded chest strap was synced together to monitor HR. To elicit a HR response, the Bruce Protocol, a maximal graded exercise testing (GXT), was utilized for this research (Eston et al, 2012). As smartphone devices have been reported to be reliable measurements of HR (Silva & Ul-Haq, 2013), each HR monitor was linked to an Apple iPhone via Bluetooth using the Wahoo Fitness Application with HR measurements measured in beats per minute (BPM) continuously across the Bruce protocol.…”
Section: Methodsmentioning
confidence: 99%
“…However, Coquart et al [5] and Eston et al [12] demonstrated that the predictions of VO 2 max are better when RPE 19 is used in incremental exercise, because RPE = 19 is more commonly reported as the feeling of exhaustion/maximal functional capacity in this type of exercise. In contrast to these studies, we showed that the Tlim estimated in constant-load exercise bouts with extrapolation to RPE 19 underestimated the measured Tlim.…”
Section: Figurementioning
confidence: 97%
“…Hence, one can expect that exercise duration until exhaustion be predicted by submaximal RPE values [8,10,11]. However, in incremental exercise the accuracy of the prediction of VO 2 max can be better when extrapolating the submaximal RPE (RPE ≤ 17) to RPE19 in comparison to RPE20 [5,12]. It may be suggested that the predictions are better when RPE = 19 is used, since previous researches have already shown that an RPE = 19 is more commonly reported as the feeling of exhaustion/maximal functional capacity [9,13].…”
Section: Introductionmentioning
confidence: 97%